Peran Partai Politik Dalam Mencegah Praktik Oligarki di Indonesia - L, Lazarus (Media Hukum Indonesia (MHI), 2024)
This article explicitly examines the role of political parties in preventing oligarchic practices in Indonesia, a complex phenomenon that threatens the national democratic system. The study aims to explore the institutional capacity of political parties in transforming the power structure dominated by a group of elites using library research methods and critical analysis of various regulations and political documents. The results of the study indicate that the institutional capacity of political parties in preventing oligarchy is still very limited. Structural and cultural factors that support the development of oligarchic practices include a non-transparent political funding system, a culture of patronage, a recruitment mechanism based on primordialism, and a symbiotic network of interests between political elites. The study identifies a number of oligarchic mechanisms, including: concentration of economic resources in a handful of elites, formation of political dynasties, control over the bureaucracy, and manipulation of political narratives through the media. The existing legal framework, such as Law Number 2 of 2008 concerning Political Parties and the amended 1945 Constitution, has normatively attempted to limit these practices, but its implementation is still very weak. The conclusion of the study confirms that preventing oligarchy requires a multidimensional approach that does not merely focus on regulatory aspects, but rather a fundamental transformation in the national political culture. It requires ongoing commitment from all components of the nation to realize a democratic, transparent, and just political system.